Impact of jet fuel hedging on firm value : a study on global airlines. - Quah, Hui Li. (2011)
This paper studies the impact of jet fuel hedging on the firm value of an airline. Using a sample of 47 airline companies from 15 countries between years 2000 to 2009, we look into the relationship between hedging decisions and firm value for two different sub-samples. In our sub-sample study on US and non-US airlines, we find that hedging for US airlines is significantly and positively correlated with firm value while there is no significant relationship for non-US airlines. For our sub-sample study on stable and volatile jet fuel prices, hedging is found to add value to airlines only during stable periods but no significant relationship was observed during volatile periods. We also find three factors, namely managerial shares and options holdings, financial distress costs and the presence of alternative hedging mechanism that have significant bearing on airlines’ hedging decisions. Upon understanding how hedging value adds across different regions and periods of fuel price volatility, investors can pay more attention to these three factors in order to accurately predict and assess airlines’ hedging decisions. This will certainly aid them in making better-informed investment decisions.